PEMBERDAYAAN EKONOMI MASYARAKAT DESA BONGO III KECAMATAN WONOSARI KABUPATEN BOALEMO - Sukrianto Sukrianto; Fibriyanti Lakoro (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Economic empowerment can be realized through several targets that focus on alleviating poverty, creating jobs, increasing people's welfare and democracy in politics. The purpose of implementing community service is to find out that the implementation of empowerment for the Bongo III Village community can run well. The method of implementing community service activities used is the preparation of materials and data on community economic empowerment activities in Bongo III Village. Education in the form of socialization to the community related to income, competence and micro-economic development in the implementation of community service. Evaluation of activities for collaboration with Bongo III Village Government partners. The results of community service can be explained that increasing income, competence and development as well as supporting village governments in realizing microeconomic empowerment in order to solve problems encountered. Keywords: Empowerment, Community, Economy, Village